2007
DOI: 10.1161/01.hyp.0000250086.06137.fb
|View full text |Cite
|
Sign up to set email alerts
|

Role of Renal Medullary Heme Oxygenase in the Regulation of Pressure Natriuresis and Arterial Blood Pressure

Abstract: Abstract-Recent studies have demonstrated that inhibition of renal medullary heme oxygenase (HO) activity and carbon monoxide (CO) significantly decreases renal medullary blood flow and sodium excretion. Given the crucial role of renal medullary blood flow in the control of pressure natriuresis, the present study was designed to determine whether renal medullary HO activity and resulting CO production participate in the regulation of pressure natriuresis and thereby the long-term control of arterial blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 49 publications
4
73
1
Order By: Relevance
“…The effect of TALH-specific induction of HO-1 on sodium transport in the TALH is supported by the observation that renal medullary inhibition of HO-1 was associated with increases in sodium and water reabsorption and development of salt-sensitive hypertension. 3 In contrast, previous studies have shown that the HO metabolite, carbon monoxide, enhanced sodium chloride reabsorption in isolated TALH tubules by stimulation of the apical 70-pS K+ channel. 12 One potential mechanism by which induction of HO-1 in TALH can decrease sodium transport is through antioxidant actions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The effect of TALH-specific induction of HO-1 on sodium transport in the TALH is supported by the observation that renal medullary inhibition of HO-1 was associated with increases in sodium and water reabsorption and development of salt-sensitive hypertension. 3 In contrast, previous studies have shown that the HO metabolite, carbon monoxide, enhanced sodium chloride reabsorption in isolated TALH tubules by stimulation of the apical 70-pS K+ channel. 12 One potential mechanism by which induction of HO-1 in TALH can decrease sodium transport is through antioxidant actions.…”
Section: Discussionmentioning
confidence: 86%
“…1 In the renal tubules, increases in perfusion pressure increase CO levels, and inhibition of HO activity results in significant attenuation of pressure natriuresis and development of salt-sensitive hypertension. 3 These data suggest an important role for HO and its metabolites in the regulation of both renal function and blood pressure.…”
mentioning
confidence: 90%
“…[22][23][24][25] Carbon monoxide also dilates blood vessels by directly activating potassium channels in vascular smooth muscle cells (SMCs). Stanford et al reported that CO can inhibit 2.…”
Section: Vasodilationmentioning
confidence: 99%
“…82 However, results from whole-animal studies in which the levels of HO are altered have not supported an antinaturetic function of CO in the kidney. Recent studies by Li et al 83 have documented an increase in CO production in the renal medulla in response to increases in renal perfusion pressure. Because increases in Figure 2.…”
Section: Co and The Kidney: Beyond The Vasculaturementioning
confidence: 99%
“…85 Lastly, chronic inhibition of HO in the renal medulla attenuates pressure-natriuresis and hypertension in response to increases in sodium intake. 83 Whether salt-sensitive hypertension resulting from inhibition of HO in the medulla is the result of changes in medullary blood flow or alterations in tubular function is not known and warrants further investigation. CO signaling in renal tubular epithelial cells has not been extensively studied; however, because it uses similar signaling pathways as NO in the vasculature, is it possible that CO is able to activate similar pathways as NO in tubular epithelial cells.…”
Section: Co and The Kidney: Beyond The Vasculaturementioning
confidence: 99%